UNITY OF NATIONALITY AND UNIVERSALITY IN THE UZBEK NATIONAL MENTALITY - T. H. Qurbonov (American Journals, 2023)
In the article, if we consider the social imagination, mood, behavioral norms, experiences, knowledge, needs, values and ideals of the Uzbek people under the influence of the unity of nationality and universality in the Uzbek national mentality, be scientifically analyzed that they all contain elements of nationality and universality.
Keywords: Uzbek national mentality, nationality, universality, social progress, new way of life, relations with other nations and peoples, public mood, national norms of behavior, national experience, national needs, national values and ideals.